2012
DOI: 10.1107/s1600536812032813
|View full text |Cite
|
Sign up to set email alerts
|

(R,E)-3-(4-Chlorophenyl)-1-phenylallyl 4-nitrobenzoate

Abstract: The title compound, C22H16ClNO4, adopts a conformation in which the phenyl ring plane forms similar dihedral angles with the nitrobenzoate C6 ring [76.97 (8)°] and the chlorophenyl group [76.95 (8)°]; the dihedral angle between the chlorophenyl and nitrobenzoate rings is 66.43 (8)°. In the crystal, π–π stacking is observed between the latter two planes, with a dihedral angle of 1.79 (8)° and a centroid&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sharpless kinetic resolution followed by acylation was used for synthesis of optically active 1 and 2 . The absolute configuration of ( R )- 1 was confirmed by X-ray diffraction analysis . The precursors for laser-flash measurements, 8 and 9 , were generated in situ from the mixture of 1-(4-chlorophenyl)-3-phenylallyl and 3-(4-chlorophenyl)-1-phenylallyl chlorides ( 11 ) synthesized from 3 using the procedure from ref and 1,2,3,4,5,6-hexahydro-1,3a,6,8-tetraazaphenalene ( 12 ) obtained as reported by David and co-workers .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharpless kinetic resolution followed by acylation was used for synthesis of optically active 1 and 2 . The absolute configuration of ( R )- 1 was confirmed by X-ray diffraction analysis . The precursors for laser-flash measurements, 8 and 9 , were generated in situ from the mixture of 1-(4-chlorophenyl)-3-phenylallyl and 3-(4-chlorophenyl)-1-phenylallyl chlorides ( 11 ) synthesized from 3 using the procedure from ref and 1,2,3,4,5,6-hexahydro-1,3a,6,8-tetraazaphenalene ( 12 ) obtained as reported by David and co-workers .…”
Section: Methodsmentioning
confidence: 99%
“…The absolute configuration of (R)-1 was confirmed by X-ray diffraction analysis. 68 The precursors for laser-flash measurements, 8 and 9, were generated in situ from the mixture of 1-(4-chlorophenyl)-3-phenylallyl and 3-(4-chlorophenyl)-1phenylallyl chlorides (11) synthesized from 3 using the procedure from ref 69 and 1,2,3,4,5,6-hexahydro-1,3a,6,8-tetraazaphenalene (12) obtained as reported by David and co-workers. 70 Detailed descriptions of HPLC experiments, laser-flash kinetic measurements, and NMR product studies as well as all synthetic procedures can be found in the Supporting Information.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%